Filicopsothrips genus recorded from China, with description of a new species (Thysanoptera: Thripidae) - Li, Yajin; Li, Yajin; Yuan, Shengyong; Zhang, Hongrui (Zootaxa, 2020)
Dendrothripinae is a small sub-family in Thripidae which has a characteristically sinuate metathoracic endofurca reaching into the mesothorax. This structure is associated with the large muscles that are involved in jumping, and a similar metathoracic furca occurs in some Panchaetothripinae members as well as Trachynotothrips in the Thripinae (Mound 1999; Masumoto & Okajima 2005). There are 12 extant genera and more than 100 species of Dendrothripinae, almost all feeding on leaves (ThripsWiki 2020). A few species are considered as pests, like Dendrothrips minowai and Pseudodendrothrips mori that damage the tea plant and mulberry respectively. An identification key to world genera of Dendrothripinae (except Projectothripoides) is available (Mound & Tree 2016), and 14 species representing six genera are recorded in Japan (Masumoto & Okajima 2017). Mirab-balou et al. (2011) provided a list of thrips in China including 15 Dendrothripinae species representing three genera: Asprothrips, Dendrothrips, and Pseudodendrothrips. Subsequently, three new species of Asprothrips have been described from this country (Tong et al. 2016, Wang & Tong 2017) and two other genera, Edissa and Ensiferothrips, were found in Southern China (Zhang et al. 2018). Just recently, Wang et al. (2019) provided a key to 10 Dendrothrips species from China, including one new species. Therefore, five genera and 26 species of Dendrothripinae are recorded in China up to now (Zhang et al. 2018).